Proceedings of the URECA@NTU 2022-2023 - Students of URECA Programme (2024)
The "Proceedings of URECA@NTU 2022-23" represents a curated collection of exceptional research papers produced during the 2022-23 academic year. These papers encompass URECA, Interdisciplinary-URECA, and Final Year Project-URECA initiatives, all crafted under the dedicated guidance of respective URECA supervising professors.